Hubungan Tingkat Pengetahuan Pengasuh dengan Pola Asuh Makan dan Status Gizi Balita di Puskesmas Sangkrah Surakarta - Agil Wahyu Wicaksono; Arsita Eka Prasetyawati; Kusmadewi Eka Damayanti (Nexus Kedokteran Komunitas, 2013)
Background:Recently the role of mothers in child parenting replace by caregivers because many mothers also act as workforces. The role of parenting especially during meal is very important in determining the nutritional status of children. This studyaim is to determine whetherlevel ofknowledgehas strong relationshipwithfeeding patternandnutritional status of children. Methods:This studyis anobservationalstudywith crosssectionalanalytic. The researchwas conducted inApril-June2013 in theworking area ofSangkrahHealth Center, Surakarta. Sample of121caregiversandtheir childrenwereselectedby multistage areasampling .Examined variables includingcaregiverslevelof knowledgeas independent variable, and feeding patternandnutritional status of childrenas dependent variable. ThisresearchusesCaregiversFeedingStyleQuestionnairetodeterminefeeding patternandQuestionnaire of Knowledge Leveltomeasure thelevel ofcaregiversknowledge. Bothquestionnaireshave beentestedfor validity and reliability. Nutritional status ismeasuredbystandard anthropometry method. Data wereanalyzedby SPSS 17 for Windows usingKendall's Taumodels. Results:This studyshows there is no significant correlation between the degree ofcaregivers knowledge andfeeding pattern(correlation coefficient = 0.132; degree of significance = 0.110) besides there is also no significant correlation between the degree ofcaregivers knowledgeand childrensnutritional status(correlation coefficient = 0.030; degree of significance = 0.716). Conclusions:There is nostatistically significantrelationshipbetween thedegree ofcaregiversknowledgewithfeeding patternandthe nutritional status ofchildren. Keywords:Degree of caregivers knowledge, feeding pattern, nutritional status of children.